Relevansi Baptis dalam Konsep Manunggaling Kawula Gusti. Korelasi Iman dan Budaya dalam Terang Teologi Budaya-Tandingan - Nada, Yoesi Prasetya (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
The focus of this study is to observe the encounter between the Christian Faith and the Cultural Tradition of Kejawen in the light of the contextual theology, such as the counter-culture model. The subject of this research is mainly the Catholics who make the values of Kejawen still alive. The author chose East Java, particularly the Catholics of the two dioceses of Surabaya and Malang as his research field and resource persons. The methodology used in this study is phenomenological approach, through a period of field research and in-dept interviews in unity with literature studies. From this study the author found out a connection between the Christian faith and the Kejawen tradition, as well as its implications for the lives of the faithfuls who are consistently in corporating or personalizing in themselves these two traditions.